“One Pot” Enzymatic Synthesis of Caffeic Acid Phenethyl Ester in Deep Eutectic Solvent - Maria Roberta Tripon; Camelia Tulcan; Simona Marc; Dorin-Dumitru Camen; Cristina Paul (Biomolecules, 2025)
Caffeic acid phenethyl ester (CAPE) represents a valuable ester of caffeic acid, which, over time, has demonstrated remarkable pharmacological properties. In general, the ester is obtained in organic solvents, especially by the esterification reaction of caffeic acid (CA) and 2-phenylethanol (PE). In this context, the purpose of this study was the use of the “one pot” system to synthesize CAPE through biocatalysis with various lipases in a choline-chloride-based DES system, employing the “2-in-1” concept, where one of the substrates functions as both reactant and solvent. The synthesis process of CAPE is contingent on the molar ratio between CA and PE; thus, this factor was the primary subject of investigation, with different molar ratios of CA and PE being studied. Furthermore, the impact of temperature, time, the nature of the biocatalyst, and the water loading of the DES system was also examined. This ‘green’ synthesis method, which has demonstrated encouraging reaction yields (%), could secure and maintain the therapeutic potential of CAPE, mainly due to the non-toxic character of the reaction medium.